Analisis Knowledge Management Dan Kualitas SDM Terhadap Kinerja Bisnis Melalui Inovasi Sebagai Variabel Mediasi Pada UMKM - Nining Yuningsih; Adi Maryadi; Rustianah Rustianah (Universitas Islam Kadiri, 2023)
This study was conducted to provide empirical evidence regarding the effect of knowledge management and HR quality on MSME business performance through innovation as a mediating variable. This study uses a sample of MSMEs engaged in the culinary sector in the Central Cikarang area. Sampling using purposive sampling method with a significance level used of 0.05 and analyzed using the PLS (Partial Least Square) application. Based on the results of the analysis, Product Innovation, Product Quality, and Accounting System have a positive and significant effect on SME performance. The results of this study are knowledge management and quality of human resources have a positive influence on innovation. Knowledge management variables have no influence on the performance of SMEs. However, the knowledge management variable has a positive influence on innovation. Then the innovation variable has a positive influence on the performance of MSMEs. And innovation mediates the influence between knowledge management and HR quality on the performance of MSMEs.